Method Effects and Measurement Invariance Testing for Korean Stress Mindset Scale - Park, Daeun (Korean Journal of Industrial and Organizational Psychology, 2022)
Stress mindset refers to implicit beliefs about the effects of stress. Although academical interests in stress mindset are growing, we know next to nothing about whether the original stress mindset scale, developed by Crum and colleagues (2013), can be used for working professionals in Korea. To examine whether the same stress mindset scale can be used in Korean adults with different occupations, we recruited college students and working professionals in finance, medicine, and education (N=531) and asked them to complete stress mindset and perceived stress questionnaires. Findings from a confirmatory factor analysis found no evidence for method effects in the original 8-item stress mindset scale. Furthermore, the results indicated that 4-item stress mindset scale, measuring debilitating effects of stress (Stress Mindset-N4), fits data better than the original 8-item scale and 4-item mindset scale, measuring enhancing effects of stress (Stress Mindset-P4). Measurement invariance testing of Stress Mindset-N4 supports configural, metric invarianc, and scalar invariance. Furthermore, the scale scale reliably predicts perceived distress.